Factors affecting the profitability of banks - Evidence from Serbia's banking sector - Miloš Đaković; Nada Milenković; Jelena Andrašić (Management)
Research Question: In the research, the authors investigate the effect of certain bank-specific, industry-specific, and macroeconomic factors on the profitability indicators of banks in the Republic of Serbia. The main question of the study is what factors have a relationship with profitability indicators and which of them has the most statistically significant impact. Motivation: Based on the research of (Fidanoski et al., 2018; Katusiime, 2021; Horobet et al., 2021), the authors intend to investigate the effects of certain factors on the profitability of the banking sector of the Republic of Serbia. The research should serve as a good indicator for banks to understand exactly which factors have the greatest impact on profitability. Idea: The essence of the research is precisely the discovery of the factors that have the most significant statistical effect on profitability indicators of banks, namely ROA (Return on assets), ROE (Return on equity), and NIM (Net interest margin). Data: The data includes a sample of 22 banks currently operating in the banking market of the Republic of Serbia. The research covers the period from 2014 to 2021 and includes a total of 174 observations. The dependent variables used are ROA, ROE, and NIM as representatives of bank profitability, while the independent variables are divided into three main units, bank-specific, industry-specific and macroeconomic factors. Tools: The research was carried out using the statistical software Eviews. The research includes the application of descriptive statistics and correlation methods. Further analysis includes the unit root test and the variance inflation factor analysis to check for stationarity and multicollinearity of the data. After testing, the authors establish a panel regression model using random and fixed effects, applying the Hausman test to establish a more valid model. Findings: Based on the performed analysis, we conclude that in the case of ROA and ROE, the variables that have the most significant influence on these indicators are liquidity indicator, the level of operating profit, capital adequacy, and loans. While liquidity, loans, and bank sector indicator such as HHI have the most significant effect on NIM. The study also showed that GDP annual growth does not have a statistically significant effect on profitability in the case of banks in the Republic of Serbia. Contribution: The paper contributes to the literature by empirically testing how certain factors affect the profitability of banks in the banking sector of the Republic of Serbia.